2020
DOI: 10.1016/j.jshs.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Does endurance training improve red blood cell aging and hemorheology in moderate-trained healthy individuals?

Abstract: Highlights Endurance training has beneficial effects on red blood cell aging and function. Improved hemorheological effects are observed in endurance-untrained individuals after a 6-week running training. A shift to more young red blood cells is observed after the training. Physical performance and blood parameters increased after the training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…In support, RBC deformability decreased after a 30 min intense cycling test, pointing to an accumulation of damage during the bout. Indeed, training results in increased RBC turnover [ 72 ] and a younger overall RBC population [ 73 ]. Furthermore, RBCs from endurance athletes tend to be more deformable [ 74 ], which suggests that these cells have more “youthful” characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In support, RBC deformability decreased after a 30 min intense cycling test, pointing to an accumulation of damage during the bout. Indeed, training results in increased RBC turnover [ 72 ] and a younger overall RBC population [ 73 ]. Furthermore, RBCs from endurance athletes tend to be more deformable [ 74 ], which suggests that these cells have more “youthful” characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…While these matrices possess unique advantages in their own right, such as the ability to measure freely circulating metabolites between tissues as is the case with plasma, they disregard the metabolism of circulating blood cells by nature of their collection methods. As appreciation is growing with respect to blood cell adaptations to exercise (Bizjak et al, 2019;de Oliveira Ottone et al, 2019;Estruel-Amades et al, 2019;Shi et al, 2019;Uchida et al, 2019), whole blood analysis enables a more complete representation of physiology. Furthermore, this sample collection is less labor intensive than serum or plasma isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that glutathione and PPP intermediates are intracellular metabolites, it is likely that the major contributors to these pools in whole blood are red blood cells (RBCs), by far the most abundant cell in both circulation and the human body (Sender et al, 2016). While exercise promotes erythropoiesis due to increased oxygen demand and need to replenish RBC populations in response to elevated hemolysis (reviewed in Mairbäurl, 2013) effects on RBC circulatory lifespan have only recently been appreciated (Bizjak et al, 2019). One of the hallmarks of RBC aging both in circulation (Lutz and Bogdanova, 2013) and in the blood bank (Nemkov et al, 2015;Yoshida et al, 2019) an environment that accelerates RBC aging (D'Alessandro et al, 2015) is the accumulation of oxidative stress markers including oxidized glutathione and allantoate.…”
Section: Discussionmentioning
confidence: 99%
“…RBC-NOS generated NO was shown to increase S-nitrosylation of the cytoskeletal proteins α- and β-spectrin which was associated to increased RBC deformability (Grau et al, 2013). These reaction routes are well described for mechanical stimulation (Ulker et al, 2009, 2010; Kuck et al, 2019), endurance sports (Suhr et al, 2012; Koliamitra et al, 2017; Tomschi et al, 2018b; Bizjak et al, 2019), but also other types of sport were shown to affect RBC-NOS/NO pathway and RBC deformability (Bizjak et al, 2018). The impact of WB-EMS stimuli on the RBC-NOS/NO signaling pathway has been first shown by Filipovic et al (2015) suggesting that WB-EMS affects RBC deformability with acute changes being explained by increased RBC-NOS activation while chronic changes in RBC deformability did not involve RBC-NOS activation.…”
Section: Discussionmentioning
confidence: 88%